Catalytic performance of Ni/MgO catalyst in methane dry reforming - Al-Swai, B.M.; Osman, N.B.; Abdullah, B. (American Institute of Physics Inc., 2017)
Methane dry reforming to synthesis gas over nickel catalysts supported on magnesium oxide has been studied. The support was prepared via co-precipitation method using ammonia solution (20 wt in water) as the precipitating agent. 10 wt of Ni metal was impregnated to form Ni/MgO catalyst. The prepared catalyst was characterized by different techniques, such as XRD, BET, SEM, and TGA analysis. The effect of reaction conditions on the conversions of CH4 and CO2, selectivity of H2 and CO, and carbon deposition were investigated in a tabular furnace reactor. The catalyst afforded as high as 93 CH4 conversion at 900 °C. The catalyst has also shown excellent stability during reaction at relatively higher space velocity (1.8×104 ml g-1 h-1) and 800 °C reaction temperature. TGA characterization of spent catalyst has shown lesser magnitude of carbon deposition on the surface of the catalyst at 900 °C. © 2017 Author(s).